Analysis of the Feasibility and Effectiveness of Ethnoscience-Based Science Learning Tools for Improving Students' Science Literacy: A Review - Ansumarwaty, Febiyanti (Balai Publikasi Indonesia, 2023)
In the 21st century, cultural values among students began to fade due to the development of increasingly sophisticated technology, so that efforts are needed to reintegrate these cultural values through learning or known as ethnoscience-based learning. This research is a literature study or literature review of relevant research published in the last 5 years. Based on the results of the literature review that has been done that ethnoscience-based science learning is categorized as feasible and effective in science learning.